PENGARUH BAP (Benzyl Amino Purine) DAN AIR KELAPA TERHADAP PERTUMBUHAN TUNAS PUCUK DAN KANDUNGAN SULFORAFAN BROKOLI (Brassica oleracea L. var. italica Plenck) SECARA IN-VITRO - Alfrida ., Maninggolang; Jeany Sh. Polii-Mandang; Wenny ., Tilaar (AGRI-SOSIOEKONOMI, 2018)
This study aims to know the effect of Benzyl Amino Purine (BAP) and Coconut Water on shoot bud growth and Broccoli Sulforaphane content (Brassica oleracea L. var italic Plenck). The study was conducted in the laboratory of Biotechnology Department of Aquaculture, Faculty of Agriculture of Sam Ratulangi University, Manado, that conducted from August-December 2017. This study used a Complete Randomized Design (RAL), consisting of 8 treatments and each repeated as many 4 times, so we get 32 unit experiment. The variables observed were number of buds, number of leaves, plant height, wet weight, root number and Sulforaphane content analysis. The result of research shows that analysis of variance showed that in the use of Benzyl Amino Purine (BAP) concentration 3 ppm tends to increase the number of leaves aged 4 Weeks After Culture (MSK) and increase the number of shoots age 2 and 6 Weeks After Culture (MSK). Benzyl Amino Purine (BAP) 3 ppm can increase the wet weight of age 6W eeks After Culture ((MSK). Coconut water 20% tends to increase the number of leaves at age 6 Weeks After Culture (MSK) and increase the number of shoots aged 6 Weeks After Culture (MSK), while for combination of 3 ppm Benzyl Amino Purine (BAP) and coconut water 20% tends to increase the number of leaves aged 2 Weeks After Culture (MSK) and the number of shoots aged 2 Weeks After Culture (MSK). Combination of coconut water and Benzyl Amino Purine (BAP) is not detected by the content of Sulforaphane.